E-Procurement and effectiveness of government goods and services procurement: case study in Singkawang, the province of west Kalimantan, Indonesia - Haryono Haryono (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Singkawang City is one of the cities in The Province of West Kalimantan that has implemented E-Procurement as a system for goods and services procurement. The process of procuring goods and services in Singkawang City can be accessed through the integrated online official website. Potential problems still arise in the process of procuring goods and services starting from planning, preparation, selection of suppliers, and handover of goods / services. The purpose of this study was to investigate readiness from local government officials of the Singkawang City in carrying out the e-procurement process. Support from leaders is needed so this system can run smoothly. The research data are primary data derived from questionnaires survey. From all government institutions in Singkawang City, there are 35 Procurement Service Unit staffs and all of them are taken as respondents in this study. The data collected was processed by linear multiple regression. The results showed that the implementation of e-procurement had a significant positive effect on the effectiveness of the procurement of goods and services and leader support was proven to be a strengthened variable to the effect of the implementation of e-procurement on effectiveness of the goods and services procurement.